EVALUATING THE TRUE PERFORMANCE OF LEADERS - Friedman, Hershey H.; Gerstein, Miriam; Hertz, Sarah (Journal of Accounting, Ethics & Public Policy, JAEPP, 2023)
We live in the age of post-truth where lying has become so acceptable that we have numerous euphemisms for deceit. It has become difficult to evaluate the true performance of leaders since they have no problem taking credit for the work of others and spinning the truth so that it appears that they have done a stellar job. Many leaders are more interested in form than substance. This paper discusses the problem of evaluating the performance of corporate leaders and provides a new paradigm for rating CEOs that includes factors that provide long-term value such as efficiency, creating meaningful work, employee engagement, customer satisfaction, and diversity.